CLEBSH-GORDAN COEFFICIENTS IN QUANTUM APPLICATIONS - Zhusupov, M.A.; Kabatayeva, R.S. (Recent Contributions to Physics, 2021)
Questions concerning Klebsh-Gordan coefficients’ quantum theory various applications are considered.